Seismic performance of water storage under the different earthquake loading - Norsyahirah Haifaa, Mohd Arriffin (2018)
Earthquakes often cause severe damage to buildings such as shear failure and bending shear failure mode in beams, axial failure in column and cracks in connection. The elevated water tank is one of the affected structure caused by an earthquake and it is necessary to be functional after a severe earthquake for suffering from post-earthquake fire and for others domestic purpose. These study reports present the analysis and design of modal analysis, response spectrum and time history analysis of an elevated water tank using SAP2000 as a software analysis. The water tank is subjected to a dead load, live load, self-weight and seismic load. A seismic load calculation is done by follow Eurocode 8 2004. The capital analysis gives the natural frequency of the structure and time history where define the behavior of the structure in certain time interval against various functions such as velocity, displacement, acceleration, shear force, and bending moment.